Barriers and critical success factors applying cleaner production: a survey with Brazilian specialists - Canal Vieira, Leticia; Gonçalves Amaral, Fernando (Brazilian Journal of Operations & Production Management, 2017)
Cleaner Production is an initiative seeking for achieving sustainable development goals. Yet, it has not been satisfactorily disseminated in Brazilian industries. The purpose of this article was identifying the barriers and critical success factors, considering both the external and internal Brazilian environment. A survey was conducted among the professionals involved with the subject of Cleaner Production in Brazil, reaching 185 respondents. Data was analyzed using the Principal Component Analysis. The results indicated that the main success factors concern the organization characteristics, and are related to culture, strategic planning and resources for the implementation of Cleaner Production. In the case of barriers, it can be highlighted the inadequate vision and culture of organizations, followed by the lack of support from the external environment. Contrary to other studies, economic aspects did not seem to be crucial in the opinion of respondents. When measures that can be taken for a more effective dissemination of CP in Brazil are approached, it can be perceived that a repositioning of the external environment (government, other companies, academia, and consumers) is necessary, acting as a strong incentive and support for applying CP.